Platelets regulate leucocyte responses to Toll‐like receptor stimulation. Issue 7 (27th July 2018) - Hally, Kathryn E; La Flamme, Anne C; Harding, Scott A; Larsen, Peter D
Abstract: Objectives: Platelets are important regulators of vascular thrombosis and inflammation and are known to express Toll‐like receptors (TLRs). Through TLRs, platelets mediate a number of responses by interacting with leucocytes. Here, we report the extent to which platelets modulate in vitro peripheral blood mononuclear cells (PBMCs) and granulocyte responses to TLR4, TLR2/1 and TLR2/6 stimulation in healthy subjects. Methods: Peripheral blood mononuclear cells and granulocytes from 10 healthy volunteers were cultured alone or cocultured with platelets. Cultures were left unstimulated or stimulated with 1 or 100 ng mL −1 of either LPS (TLR4 agonist), Pam3CSK4 (TLR2/1 agonist) or fibroblast‐stimulating lipopeptide (FSL)‐1 (TLR2/6 agonist). Neutrophil activation (CD66b expression), monocyte activation (HLA‐DR), granulocyte elastase production and PBMC cytokine and chemokine production were examined. Results: Platelet coculture decreased neutrophil CD66b expression in response to LPS, Pam3CSK4 and FSL‐1, and modestly decreased monocyte HLA‐DR expression in response to low‐dose LPS. Platelets reduced granulocyte elastase secretion in response to low doses of all TLR agonists tested. In response to LPS, platelet coculture reduced IL‐6, tumor necrosis factor (TNF)‐α and MIP‐1β production, and increased IL‐10 production by PBMCs. In response to FSL‐1, platelets increased IL‐6, IL‐10 and MIP‐1β production, but reduced TNF‐α production. Platelet coculture did not alter PBMC cytokine/chemokine production in response to Pam3CSK4. Conclusion: This study challenges the notion that platelets act solely in a pro‐inflammatory manner. Rather, platelets are complex immunomodulators that regulate leucocyte responses to TLR stimulation in a TLR agonist‐specific manner. Platelets may modulate leucocyte responses to dampen inflammation, and this platelet effect may play an important role in reducing inflammation‐mediated host damage. Abstract : Platelets are important regulators of vascular thrombosis and inflammation, and are known to express a number of Toll‐like receptors (TLRs). In this study, we show that platelets dampen a number of leukocyte responses to TLR stimulation, in a TLR agonist‐specific manner. This study challenges the notion that platelets act solely in a pro‐inflammatory manner, and this dampening platelet effect may play an important role in reducing inflammation‐mediated host damage.